Modelling Christianisation : a geospatial analysis of the archaeological data in the rural church network of Hungary in the 11th-12th centuries /: a geospatial analysis of the archaeological data in the rural church network of Hungary in the 11th-12th centuries. (2022) - Vargha, Mária
No abstract available